The Analysis Technological Pedagogical Content Knowledge (TPACK) of Natural Science Secondary School Teachers' Based on School Accreditation - Herry Suryanto; Septi Budi Sartika; Mochamad Nashrullah (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the ability of natural science secondary school teachers’ to use information and communication technology to assist the learning process (Technological Knowledge), the ability of natural science secondary school teachers’ to manage classes (Pedagogical Knowledge), and the ability of natural science secondary school teachers’ to mastery learning (Content Knowledge). This research is a qualitative research with a phenomenological approach. The research subjects were a natural science teachers’ at SMP Negeri 1 Prambon who was accredited A and a natural science teachers’ at SMP Perjuangan Prambon who was accredited B. Data collection techniques in this study used documentation, observation and interviews. The data analysis phase uses the Miles and Huberman model. Test the validity of the data using technical triangulation. Based on the research results, it was revealed that the ability of natural science secondary school teachers’ in mastering information and communication technology (Technological Knowledge) is quite good. Teachers at schools accredited A and B are quite good at operating Microsoft Word, Microsoft Power Point. Teachers at schools accredited A are not good at operating Microsoft Excel, while teachers at schools accredited B are not very good at operating Microsoft Excel. The ability of secondary school natural science teachers’ at accredited A schools to manage classes (Pedagogical Knowledge) is very good, while the ability of natural science secondary school teachers’ at schools accredited B is quite good. The ability of natural science secondary school teachers’ in schools accredited A is very good in mastering the subject matter they teach (Content Knowledge), while the ability of natural science teachers in schools accredited B is quite good. In future research it is expected to be able to uncover the TPACK of science teachers based on the length of time the teacher has been teaching or the other factor.